2019
DOI: 10.1186/s12961-019-0422-5
|View full text |Cite
|
Sign up to set email alerts
|

Health researchers’ experiences, perceptions and barriers related to sharing study results with participants

Abstract: Background: Although research participants are generally interested in receiving results from studies in which they participate, health researchers rarely communicate study findings to participants. The present study was designed to provide opportunity for a broad group of health researchers to describe their experiences and concerns related to sharing results (i.e. aggregate study findings) with research participants. Methods: We used a mixed-methods concurrent triangulation design, relying on an online surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 32 publications
4
53
0
Order By: Relevance
“…While trust was not specifically addressed in the focus groups, some participants mentioned that returning study findings could increase one's likelihood to recommend participating in research. Given the multitude of well-known, documented disparities in research participation [22][23][24][25][26][27], disseminating research results to participants could be one meaningful way to build trust and encourage future research participation [6,9,10,28,29]. Future research should assess how returning study findings impacts participants' trust and likelihood of participating in future research studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While trust was not specifically addressed in the focus groups, some participants mentioned that returning study findings could increase one's likelihood to recommend participating in research. Given the multitude of well-known, documented disparities in research participation [22][23][24][25][26][27], disseminating research results to participants could be one meaningful way to build trust and encourage future research participation [6,9,10,28,29]. Future research should assess how returning study findings impacts participants' trust and likelihood of participating in future research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Research participants are a particularly important stakeholder group given that without them, research would not proceed. While research communities generally support returning findings to participants [3][4][5][6][7], this is not a common practice among researchers [6,8]. This may be due in part to limited knowledge about ways to do so, uncertainty about the types of information to return, ethical concerns, financial constraints, or other barriers to dissemination [4,6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Other related study findings contribute to the literature by documenting researchers' perspectives and experiences about sharing results with research participants. One such study surveyed health researchers in which the majority of respondents indicated that health research results should always be shared with participants [85]; although the described barriers to results sharing and various reported reasons not to share results suggest difficulties with a "one-size-fits-all" approach to improving results sharing.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…Legal jurisdictional areas may differ in terms of the extent of sharing of results with participants. In the U.S., for instance, it is not normative for health research ethics review boards to encourage health researchers to share aggregate study findings in contrast to practices in Australia, for example [85]. A poll conducted by Research Australia in 2019 indicated that a majority of Australians were willing to share their personal health information for research purposes, in order to advance health and medical research (78%), support healthcare providers in improving patient care (68%), and to assist public health officials in tracking diseases, disabilities and their causes (61%) [86].…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…A mixed-methods concurrent triangulation design [17][18][19][20][21][22][23], with a survey that collected quantitative and qualitative data simultaneously, assessed the perceptions and barriers health researchers experience with the dissemination of results to study participants. The study protocol and general findings are provided elsewhere [24,25]. This article focuses on an in-depth examination of the perceived barriers as they were described by survey respondents.…”
Section: Methodsmentioning
confidence: 99%